Ultrasound evaluation of biopsy proven malignant breast mass - Barman, Geetanjali; Bujarbaruah, Kabita; Choudhury, Binoy Kumar; Kataki, Amal Chandra (International Journal of Research in Medical Sciences, 2020)
Background: Breast cancer is the most common malignancy in female worldwide. Ultrasound (US) is a safe and easily available modality for evaluation of breasts in females of all age groups. It can detect characteristic features of breast malignancy with high degree of accuracy. This study was undertaken with the aims to evaluate the ultrasonographic features of malignant breast mass, to identify the most commonly encountered gray scale ultrasound findings and to study the role of Doppler ultrasound in those cases. Methods: The study was conducted in Dr B. Borooah Cancer Institute, Guwahati from January 2018 to January 2019. Gray scale ultrasound including Doppler study was done in all the female patients coming with palpable breast lump or with nipple discharge and images were archived. The archived images of a total number of 108 patients with biopsy report positive for malignancy were retrospectively studied and the ultrasound findings were evaluated. Results: Most common gray scale ultrasound features for malignant breast masses were hypoechoic mass, taller than wide, irregular shape, having spiculated margins, neither posterior acoustic enhancement nor shadowing, presence of intralesional microcalcifications and surrounding echogenic halo. Hypervascularity, noticeable difference in waveform pattern between central and peripheral vessels, high resistance flow pattern with absent or reversal of diastolic flow were the common Doppler findings. Conclusions: Combination of Doppler with gray scale ultrasound has emerged as a very important technique in diagnosing malignant breast mass with high accuracy.